Thyroid Disorders and Prolactin Hormone and Their Association with Obesity in Infertile Women in a Tertiary Hospital of Nepal - Maskey, Suvana; Rijal, Hima (Journal of Institute of Medicine Nepal, 2020)
Introduction Thyroid dysfunction has profound effects on menstrual function and female fertility. Hypothyroidism is often associated with increased prolactin level which again worsens the problem. This study was done to evaluate the prevalence of thyroid disorders in infertile women attending infertility outpatient department (OPD) in Tribhuvan University Teaching Hospital (TUTH) and to determine the association of hypothyroidism and hyperprolactenemia with obesity which is not well studied in our population. Methods A hospital-based cross-sectional study was conducted in infertility OPD of TUTH reviewing women’s records who underwent infertility workup and relevant history, clinical finding and results of investigations including thyroid function test (TFT) and serum prolactin (PRL) level were documented. Descriptive and inferential statistical analyses were used to identify the prevalence and associations of predictors and outcome variables. Results Out of 213 participants, the majority of the participants were obese (90; 42.3%) with mean (±SD) body mass index (BMI) being 24.8 ± 4.5 kg/m2. The prevalence of thyroid disorder was 18.4% including hypothyroidism 13.6% and hyperthyroidism 4.8%. There was no significant association of BMI and hyperprolactinemia with thyroid disorder as well as of BMI with hyperprolactinemia however the thyroid stimulating hormone (TSH) had significant positive correlation with prolactin (r=0.23, p<0.001). Conclusion Thyroid disorders and hyperprolactinemia are commonly observed in infertile women, so they should be routinely screened during initial evaluation of infertility. As majority of the study population were obese, despite no significant association of BMI with thyroid disorder and hyperprolactinemia, the effect of weight gain on infertility cannot be overlooked.